LIVING HADITH: MARKETING PRACTICES WITH THE PRINCIPLES OF BUYING AND SELLING CASH SYSTEMS, CASH TEMPO, AND CREDIT - Zunaidi, Arif (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
The business world requires businessmen to compete with each other to win the market. One of the activities needed to dominate the market is marketing activities. With the right techniques and systems that can reach consumers, marketing choices can certainly bring in new customers or retain old ones. Some parts of marketing techniques in the buying and selling business use the principles of buying and selling cash, cash tempo, and credit. One of the businessmen who applies this principle is Mega Elektronik & Handphones, located in Nganjuk city. Where in its business activities, the three sales methods are carried out in order to attract consumers. This study uses a qualitative method with a descriptive approach. The purpose of this study is to analyze the business activities owned by Mega Elektoonik & Mobile in terms of hadith. The results of this research conclude that the activities carried out by this business do not conflict with the hadith. This means that of the three ways in which sales activities are carried out, they are still within the corridor of not violating the applicable laws in sharia marketing. Dunia bisnis mengharuskkan para pelakunya untuk saling bersaing demi memenangkan pasar. Salah satu aktivitas yang dibutuhkan untuk menguasai pasar adalah kegiatan marketing. Dengan tehnik yang tepat dan system yang dapat menjangkau konsumen, maka pilihan marketing tentunya dapat meendatangkan para pelanggan baru atau mempertahankan pelanggan lama. Beberapa bagian dari tehnik marketing dalam bisnis jual beli adalah menggunakan prinsip jula beli cash, cash tempo dan kredit. Salah satu pelaku yang menerapkan prinsip tersebut adalah Mega Elektonik dan handphone yang berada di kota Nganjuk. Dimana dalam kegiatan bisnisnya, tiga metode penjualan tersebut diakukan demi menarik para konsumen. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Tujuan dari penelitian ini adalah untuk menganalisa dari kegatan usaha yang dimiliki oleh Mega Elektoonik & Handphone ditinjau dalam hadist. Hasil dari peneltian ini menyiimpulkan bahwa kegiatan yang dilakukan oleh usaha ini tidak bertentangan dengan hadist. Artinya dari ketiga cara dalam keegiatan penjualan tersebut masih dalam koridor tidak menyalahi hukum yang berlaku dalam marketing syariah.